Cancer Incidence Among People With a Prior Hospital Record of Depression in Scotland, 1991–2019: A Cohort Study - Thulani Ashcroft; Kelly Fleetwood; Christine Campbell; Caroline A. Jackson (Cancer Medicine)
ABSTRACT Objective Current evidence on the association between depression and cancer risk is conflicting, with little understanding of how associations vary by time period or sociodemographic factors. We aimed to compare cancer incidence in people with versus without a previous hospital admission record for depression, by sociodemographic factors and over time. Methods We conducted a cohort study using national linked data in Scotland from 1991 to 2019. We calculated sex‐stratified age standardised incidence rates for all cancers, lung, female breast, colorectal and prostate cancer, and used quasi‐Poisson regression models to obtain sex‐specific estimates of cancer incidence and relative risks of cancer in those with versus without a prior hospital admission record of depression. Results There were 128,654 people with a hospital record of depression with 12,802 incident cancers and 847,656 cancers among those without depression. Age‐standardised cancer incidence rates were higher in both males and females with versus without depression. Depression was associated with a 20%–30% increased risk of all cancers combined, a difference that did not vary by sex, age or deprivation and persisted over three decades. Depression was associated with higher risks of lung (RR 1.79, 95% CI 1.70–1.88) and colorectal cancer (RR 1.12, 95% CI 1.05–1.19), but not breast or prostate cancer. Conclusions We identified an entrenched disparity in cancer incidence by depression status. Further research should identify underlying mechanisms and inform cancer prevention strategies in this vulnerable group. Meanwhile, health care professionals have a key role to play in optimising physical health care for people with depression.